Measles (lecture) - L. R. Shostakovych-Koretskaya; V. V. Mavrutenkov; A. V. Cherhinets; I. V. Budayeva; O. M. Yakunina; Z. A. Chykarenko (Medičnì Perspektivi, 2019)
The article provides comprehensive review of different aspects of measles. Definition of disease, historical overview, measles in the world epidemiology and in the countries bordering Ukraine over the recent years, particularities of measles epidemiology in Ukraine are given in details. Etiology of measles virus including known genomic structure and viral proteins list, genetic changeability of the virus. Particularities of measles epidemiological process are discussed, criteria of determination of morbidity level and contagiosity of the given disease are outlined. Detailed pathogenesis of measles in different periods of disease is provided, reciprocal influence of the disease and vitamin A metabolism is given. Particularities of humoral and cellular immunological response, including those in early-aged and in patients with immune deficiency are described. Possibility of development of subacute sclerosing panencephalitis is pointed out; currently accepted causes of this complication development, its immunological and virological particularities are summarized. Pathogenetic mechanisms of rash development, complications as well as morphological changes in different organs and systems are given. The article gives both international and different clinical classifications of measles. Clinical manifestations of typical and atypical measles course are described in details by syndromes and according to disease periods. Particularities of measles course at different premorbid conditions are described. The article provides colored photos which illustrate clinical manifestations of measles manifestation on the skin and mucosa at different disease periods.